The structure of the SOLE element of oskar mRNA - Simon, Bernd (RNA, 2015)
mRNA localization by active transport is a regulated process that requires association of mRNPs with protein motors for transport along either the microtubule or the actin cytoskeleton. oskar mRNA localization at the posterior pole of the Drosophila oocyte requires a specific mRNA sequence, termed the SOLE, which comprises nucleotides of both exon 1 and exon 2 and is assembled upon splicing. The SOLE folds into a stem–loop structure. Both SOLE RNA and the exon junction complex (EJC) are required for oskar mRNA transport along the microtubules by kinesin. The SOLE RNA likely constitutes a recognition element for a yet unknown protein, which either belongs to the EJC or functions as a bridge between the EJC and the mRNA. Here, we determine the solution structure of the SOLE RNA by Nuclear Magnetic Resonance spectroscopy. We show that the SOLE forms a continuous helical structure, including a few noncanonical base pairs, capped by a pentanucleotide loop. The helix displays a widened major groove, which could accommodate a protein partner. In addition, the apical helical segment undergoes complex dynamics, with potential functional significance.